2019
DOI: 10.1177/0004867419888575
|View full text |Cite
|
Sign up to set email alerts
|

Psilocybin-assisted therapy for depression: How do we advance the field?

Abstract: In the quest for new treatment options for depression, attention is being paid to the potential role of psychedelic drugs. Psilocybin is of particular interest given its mechanism of action, its benefits in early trials and its relatively low side effects burden. This viewpoint outlines a number of key issues that remain to be elucidated about its potential use in the clinical environment, including clarification of the profile of people most likely to benefit and those who might experience adverse effects, lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In small pilot trials, psilocybin has been shown to be efficacious in treating obsessive-compulsive disorder (Moreno, Wiegand, Taitano, & Delgado, 2006), smoking addiction (Johnson, Garcia-Romeu, Cosimano, & Griffiths, 2014) and alcohol dependence (Bogenschutz et al, 2015). There are currently a large number of ongoing projects seeking to replicate and extend clinical psilocybin research within Phase II trials (see Meikle et al, 2019).…”
Section: Clinical Psychedelic Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…In small pilot trials, psilocybin has been shown to be efficacious in treating obsessive-compulsive disorder (Moreno, Wiegand, Taitano, & Delgado, 2006), smoking addiction (Johnson, Garcia-Romeu, Cosimano, & Griffiths, 2014) and alcohol dependence (Bogenschutz et al, 2015). There are currently a large number of ongoing projects seeking to replicate and extend clinical psilocybin research within Phase II trials (see Meikle et al, 2019).…”
Section: Clinical Psychedelic Researchmentioning
confidence: 99%
“…Notwithstanding some impressive results in terms of the size, speed, and the sustained nature of beneficial changes associated with psychedelics, various methodological limitations warrant caution. For example, many studies in the modern era of psychedelic research have been small (albeit with large enough effect sizes to be adequately powered in many cases), and hampered by difficulties with adequate blinding, outsized expectancy effects, and participant self-selection biases (Meikle et al, 2019;Reiff et al, 2020).…”
Section: Clinical Psychedelic Researchmentioning
confidence: 99%
“…Psilocybin, commonly known as "magic mushrooms", is a naturally occurring compound found in a variety of mushroom species. 4,10 Following ingestion, psilocybin is broken down to its psychoactive metabolite, psilocin (4-hydroxy-N, N-dimethyltryptamine). 11 Psilocin acts as an agonist to 5-HT2A serotonin receptors in the brain.…”
Section: How It Workmentioning
confidence: 99%
“…Hyperactivity of the DMN has been linked to negative self-referential and ruminating thoughts commonly associated with depression and anxiety. 4,8,10 By decreasing DMN activity, individuals experience mental flexibility leading to positive changes in attitude, mood, perspective, values, and behavior. 4,12,14 This allows patients to accept their emotions and process them.…”
Section: How It Workmentioning
confidence: 99%
See 1 more Smart Citation